Development of Power Management Circuit for Hybrid Energy Harvester - Roslee, Muhamad Faris Izzuddin (2017)
Vibration-based energy harvester has become quite an impressive method and caught many interest in powering wireless sensor networks and low power devices in these past decades. Most of the research and literature use a stand-alone energy harvester transducer, among of them are piezoelectric, electromagnetic and electrostatic. The development of power management circuit to rectify and regulate the output voltage from any energy harvesters are normally made for each of the transducer. The approach of using hybrid energy harvester which integrates both the piezoelectric and electrostatic is proposed to enhance the output voltage required to power up Internet of Things (IoT) device. This paper presents the development of power management circuit for hybrid energy harvester. A circuit which can cater two inputs from the hybrid energy harvester such as piezoelectric-electrostatic combination. The circuit composed of a full-wave bridge rectifier with a buck-boost converter running in discontinuous conduction mode (DCM) to maintain a constant input impedance through a fixed duty cycle for each of the transducers, and the usage of pulse voltage that connected to the gate MOSFET of both sources with the idea of integrating the two inputs from the transducers with a supercapacitor to store the output voltage of the energy harvester. The circuit rectifies the AC output from the hybrid energy harvester and produces a regulated DC output that is sufficient to power up the IoT device, an example in this project, NRF204L01, a single chip transceiver. The circuit is designed and simulated with Multisim to get an output voltage which is between 1.9 V to 3.6 V. The simulation result shows the output voltage generated by the circuit is 1.011 V with frequency of 100 Hz and 20 Hz for piezoelectric and electrostatic respectively. The experiment result shows the output voltage generated by the circuit is 400 mV which is lower compared to the simulation. Detailed analysis about the circuit is also discussed in this report.